Chemical and biological profiles of essential oils from Mentha spicata L. leaf from Bejaia in Algeria. Issue 3 (3rd May 2016) - Brahmi, Fatiha; Adjaoud, Abdenour; Marongiu, Bruno; Falconieri, Danilo; Yalaoui-Guellal, Drifa; Madani, Khodir; Chibane, Mohamed
Abstract: Air-dried leaves of Mentha spicata L. were collected in Bejaia location (Algeria) during 2013. The plant samples were distillated by Clevenger apparatus and the essential oils obtained were analyzed by GC and GC/MS. Fifty compounds amounting to 98.9% of the oil, were identified. The major components of the oil were carvone (48.5%), limonene (20.7%), and 1, 8-cineole (5.4%). This oil exhibited high antimicrobial activity with a high effectiveness against Candida albicans strain with a diameter of growth inhibition zones of ranging from 14.3 ± 1.5 to 44.3 ± 1.1 mm. The antioxidant activity determined by five different test systems showed that the oil exhibits moderate activity. The insecticidal activity has been tested on the adults of Rhyzopertha dominica F., the main pest of wheat. Contact and fumigant toxicity assays showed mortality percentages of 14.0 and 34.5% respectively at the dose of 2 μL/mL and the repellency percentage was 56.2% at 30 minutes.